2002
DOI: 10.1007/s11738-002-0026-4
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in growth and peroxidase activity by heavy metals in Phaseolus seedlings

Abstract: The aim of the present work was to see the effect of mercury and chromium on elongation growth of phaseolus seedlings and changes in chlorophyll content. Phaseolus seedlings were treated with two different concentrations of two heavy metals viz. mercury (0.05 mM and 0.4 mM HgCI2, and chromium (0.5 mM and 1.0 mM K2Cr207). Both mercury and chromium inhibited root and hypocotyl elongation growth. Changes in cytoplasmic and wall bound peroxidase activities were studied using guaiacot as a hydrogen donor. Peroxidas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 28 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…There is evidence that elevated levels of these scavenging enzymes provide antioxidative protection to combat the negative consequences of HM stress in the CAL ecotype. The ability of plants to effectively counteract the harmful effects of excess HM concentration is rather limited, and many studies showed the opposite tendency, in which decreased peroxidase activity was manifested in growth disturbances [74,75]. Such a relationship could also be confirmed in the SER ecotype which exhibited only a relative increase (statistically insignificant) in peroxidase activity in shoots cultivated on 1× HMs-enriched medium and their relative decrease in 2.5× HMs treatment in comparison to shoots from the control medium (Figure 8).…”
Section: Changes In Antioxidant Accumulations Are Ecotype-specificmentioning
confidence: 99%
“…There is evidence that elevated levels of these scavenging enzymes provide antioxidative protection to combat the negative consequences of HM stress in the CAL ecotype. The ability of plants to effectively counteract the harmful effects of excess HM concentration is rather limited, and many studies showed the opposite tendency, in which decreased peroxidase activity was manifested in growth disturbances [74,75]. Such a relationship could also be confirmed in the SER ecotype which exhibited only a relative increase (statistically insignificant) in peroxidase activity in shoots cultivated on 1× HMs-enriched medium and their relative decrease in 2.5× HMs treatment in comparison to shoots from the control medium (Figure 8).…”
Section: Changes In Antioxidant Accumulations Are Ecotype-specificmentioning
confidence: 99%
“…U2 location has higher amounts of Cr, Cu and Ni than U1 and U3. One of the main function of peroxidases is being a part of detoxification enzyme complex in the cell wall, which prevents damage during different kinds of stress (Parmar et al 2002). It is known that heavy metals can affect cell wall in active way (Krzesłowska 2011), therefore they could decrease peroxidases content due to its activation and use to reduction O 2 .…”
Section: Soil Analysismentioning
confidence: 99%
“…Chromium phytotoxicity has been considered to be inhibitory for plant growth, its presence in excess amount within the plant can cause stunted shoot growing, root developing poorly (Bishnoi et al, 1993;Citterio et al, 2003;Dube et al, 2003;Faisal and Hasnaim, 2005;Gbaruko and Friday, 2007). Chromium toxicity in plants also leads to leaves chlorosis, tissue necrosis, decreases enzyme activity, causes membrane damage, diminished photosynthesis and changing of chloroplast (Jain et al, 2000;Parmar et al, 2002;Du et al, 2003;Dube et al, 2003;Zayed and Terry, 2003;Scoccianti et al, 2006). The toxicity of chromium and chromium-content in plants, however, is species specific.…”
Section: Introductionmentioning
confidence: 99%